2003
DOI: 10.1084/jem.20021258
|View full text |Cite
|
Sign up to set email alerts
|

Deficiencies of GM-CSF and Interferon γ Link Inflammation and Cancer

Abstract: Chronic inflammation contributes to carcinogenesis, but the underlying mechanisms are poorly understood. We report that aged granulocyte-macrophage colony stimulating factor (GM-CSF)-deficient mice develop a systemic lupus erythematosis (SLE)-like disorder associated with the impaired phagocytosis of apoptotic cells. Concurrent deficiency of interferon (IFN)-γ attenuates the SLE, but promotes the formation of diverse hematologic and solid neoplasms within a background of persistent infection and inflammation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
135
0
5

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(146 citation statements)
references
References 31 publications
6
135
0
5
Order By: Relevance
“…Enzler et al suggested a role between GM-CSF and IFNg in the protection against tumor development, since GM-CSF/IFNg double knock-out mice, but not single knock-out mice, developed spontaneous tumors. 24 Whether this mechanism also acts on established tumors is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Enzler et al suggested a role between GM-CSF and IFNg in the protection against tumor development, since GM-CSF/IFNg double knock-out mice, but not single knock-out mice, developed spontaneous tumors. 24 Whether this mechanism also acts on established tumors is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…This pleiotropic response of T cells in the context of malignancy is reminiscent of the involvement of macrophages which are well known to include those that promote as well as those that antagonize tumor development (31). It is also reminiscent of aspects of normal physiology: thus, whereas NK cells are prototypically cytotoxic, uterine NK cells produce high amounts of cytokines, including IFN␥, but are not cytolytic and are associated with trophoblast growth and invasion of the uterus (25).…”
Section: Phenotypic Analysis Of Cd8 ؉ Til (Putative T-pro) Associatedmentioning
confidence: 99%
“…Recent reports from several groups have re-addressed this issue and provided strong evidence for the existence of an effective cancer immunosurveillance process in mice. [3][4][5][6][7][8][9][10][11] As summarized in Table 1, mice lacking specific cellular populations, such as T cells, natural killer T (NKT) cells, and/or natural killer (NK) cells, as well as specific molecules, such as interferon (IFN)-γ, interleukin (IL)-12, perforin, or tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), unequivocally show higher incidences of tumor development. Moreover, administration of IL-12 or α-galactosylceramide (α-GalCer) that can stimulate T, NKT, and/or NK cells, reduces primary tumor incidence.…”
mentioning
confidence: 99%